Seismicity Level Analysis of the West Coast of Northern Sumatra in 1964-2023 based on Spatial and Temporal Variations of Seismotectonic Parameters - Arieza, Moreno Wahyu (Journal of Experimental and Applied Physics, 2025)
Located in the subduction zone of the Indo-Australian Plate beneath the Eurasian Plate, the west coast of northern Sumatra exhibits high seismic activity, as evidenced by the 2004 Aceh earthquake (Mw9.1) and the 2005 Nias–Simeulue earthquake (Mw8.6). This study aims to analyze the spatial and temporal variations of b-values and a-values to assess rock stress accumulation and seismicity levels, as a preliminary step toward earthquake hazard mitigation. The analysis was conducted using the Maximum Likelihood method based on the Gutenberg–Richter law. Earthquake data were obtained from the USGS catalog from 1964 to 2023, with events of Mw ≥ 5.0 and focal depths shallower than 60 km, within the coordinates 2.01°S–7.54°N and 92.77°E–99.45°E. The results indicate that b-values vary from 0.53–0.57 in Nagan Raya and Aceh Singkil to as high as 2.07 in the Indian Ocean northwest of Aceh. Similarly, a-values range from 4.3 to 12.45, with the lowest values also located in Nagan Raya and Aceh Singkil. The combination of low b- and a-values in these areas suggests high stress accumulation, indicating a greater potential for future significant earthquakes. The estimated earthquake return periods for Mw ≥ 7.0, Mw ≥ 8.0, and Mw ≥ 9.0 in Nagan Raya are 17.6, 60.8, and 210.3 years, respectively, while in Aceh Singkil they are 15.7, 57.3, and 208.8 years, highlighting the urgent need for seismic hazard preparedness in these regions.